ANALISIS KEPUTUSAN INVESTASI KEUANGAN DENGAN PENDAPATAN SEBAGAI VARIABEL MODERASI PADA GENERASI MILENIAL DI KABUPATEN JOMBANG - Nur Aini Adzan Nisa; Dhani Ichsanuddin Nur (Universitas Sarjanawiyata Tamansiswa, 2026)
The trend of financial investment in Indonesia shows rapid growth, especially among millennials. However, this increasing participation has not been fully accompanied by adequate understanding of risks and financial management, leading to vulnerability to illegal investment practices. Based on this phenomenon, this study aims to analyze the influence of financial literacy, return perception, and risk perception on investment decisions, with income as a moderating variable among millennials in Jombang Regency. This research uses a quantitative method with a Partial Least Squares (PLS) approach and involves 100 respondents who are millennials in Jombang Regency. The sampling technique was purposive sampling, and data were collected using a Likert-scale questionnaire. Data analysis was performed using SmartPLS 4 to examine both direct effects and moderating effects between variables. The results show that financial literacy does not contribute to investment decisions, while return perception and risk perception do contribute to investment decisions. Additionally, income does not contribute as a moderating variable in the relationships between financial literacy, return perception, risk perception, and investment decisions. These findings emphasize that individuals’ perceptions of potential gains and risks have a greater influence than income in determining investment decisions among millennials.